Ultrasonic Analysis of Peptide- and Antibody-Targeted Microbubble Contrast Agents for Molecular Imaging of αβ-Expressing Cells - Paul A. Dayton; David Pearson; Jarrod Clark; Scott Simon; Patricia A. Schumann; Reena Zutshi; Terry O. Matsunaga; Katherine W. Ferrara (Molecular Imaging)
The goal of targeted ultrasound contrast agents is to significantly and selectively enhance the detection of a targeted vascular site. In this manuscript, three distinct contrast agents targeted to the α v β 3 integrin are examined. The α v β 3 integrin has been shown to be highly expressed on metastatic tumors and endothelial cells during neovascularization, and its expression has been shown to correlate with tumor grade. Specific adhesion of these contrast agents to α v β 3 -expressing cell monolayers is demonstrated in vitro, and compared with that of nontargeted agents. Acoustic studies illustrate a backscatter amplitude increase from monolayers exposed to the targeted contrast agents of up to 13-fold (22 dB) relative to enhancement due to control bubbles. A linear dependence between the echo amplitude and bubble concentration was observed for bound agents. The decorrelation of the echo from adherent targeted agents is observed over successive pulses as a function of acoustic pressure and bubble density. Frequency–domain analysis demonstrates that adherent targeted bubbles exhibit high-amplitude narrowband echo components, in contrast to the primarily wideband response from free microbubbles. Results suggest that adherent targeted contrast agents are differentiable from free-floating microbubbles, that targeted contrast agents provide higher sensitivity in the detection of angiogenesis, and that conventional ultrasound imaging techniques such as signal subtraction or decorrelation detection can be used to detect integrin-expressing vasculature with sufficient signal-to-noise.